Salim kepada Guru as Experiential Learning: Cultivating Respect, Love, and Tawadhu’ among Primary School Students in Indonesia - Taufikin (Al-Qalam Institute, 2024)
This study examines the practice of salim as an experiential form of character education in Indonesian primary schools. While character education is often approached through cognitive instruction and formal programs, this research explores how moral values are internalized through lived interaction embedded in school culture. Using a qualitative ethnographic design, the study was conducted over four years in three primary schools in Demak Regency, involving teachers, students, and parents as participants. Data were collected through prolonged participant engagement, in-depth interviews, documentation, and reflective field notes, and analyzed thematically to capture recurring patterns of meaning. The findings reveal that salim functions as a holistic pedagogical practice that cultivates adab, strengthens emotional relationships, and develops tawadhu through repeated, embodied interaction. Rather than operating as a symbolic gesture, salim becomes a medium through which respect, care, and humility are enacted and gradually internalized. The study highlights that character formation emerges from sustained social practice rather than isolated instruction. These findings suggest the importance of recognizing culturally grounded practices as meaningful pathways for character education, offering an alternative approach that integrates behavioral, emotional, and spiritual dimensions within everyday learning environments.